PENGARUH KOMUNIKASI EDUKATIF TERHADAP MINAT BELAJAR DI MASA PADEMI COVID 19 SMAN 8 PONTIANAK - Dikki Marianto; Mashudi Mashudi; Maria Ulfah (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2022)
Abstack This thesis is entitled "The Influence of Educational Communication on Interest in Learning During the Covid 19 Pandemic In Economics Subject Class X SMAN 8 Pontianak" the general problem in this study is "how is the Effect of Educational Communication on Interest in Learning During the Covid 19 Pandemic Period in Class Economics Subject X SMAN 8 Pontianak?” The general objective of this research is "to find out the Effect of Educational Communication on Interest in Learning During the Covid 19 Pandemic In Economics Subject Class X SMAN 8 Pontianak". The approach used in this research is a quantitative approach with quantitative methods. The data collection technique used is distributing questionnaires and documents. Respondents in this study were students of class X IIS 1-4 SMAN 8 Pontianak. Based on the results of this study, there is an effect of educative communication with students' learning interest in economics subjects in class X SMAN 8 Pontianak with the obtained data results with tcount of 7.695, so that it can be compared with ttable of 5% with a significant level of 1.661, then tcount > t table (7.695 > 1.661) Ha accepted Ho accepted. So that it shows the results that there is an influence of the two variables (X) and (Y) namely educative communication with interest in learning Keywords:Communication,Educative,Influience